2015
DOI: 10.1039/c5ra03559g
|View full text |Cite
|
Sign up to set email alerts
|

Production of biosurfactant by a Pseudomonas aeruginosa isolate and its applicability to in situ microbial enhanced oil recovery under anoxic conditions

Abstract: An isolated strain SG can produce biosurfactant under anoxic conditions and has great potential for in situ microbial enhanced oil recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 32 publications
1
52
0
Order By: Relevance
“…They aimed at a comprehensive characterization of the material and at unravelling how the rhamnolipid anions are introduced into the interlayers of LDH. ATR-IR spectroscopy for the qualitative identification of rhamnolipids produced in fermentation processes has been reported as well [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…They aimed at a comprehensive characterization of the material and at unravelling how the rhamnolipid anions are introduced into the interlayers of LDH. ATR-IR spectroscopy for the qualitative identification of rhamnolipids produced in fermentation processes has been reported as well [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Rhamnolipid with excellent properties such as biodegradability, low toxicity, antimicrobial, good surface activity and emulsi cation [1,2] and usually produced by Pseudomonas aeruginosa [3], was currently the most potential biosurfactant to apply in oil recycling [4,5] and environmental protection [6], food processing [7,8] and biomedical industry [9,10]. However, despite their potential, the industrial application of rhamnolipid was restricted seriously since the cost of rhamnolipid production was approximate ten times that of synthetic surfactant [11].…”
Section: Introductionmentioning
confidence: 99%
“…The anaerobic biosynthesis of rhamnolipids has important research and practical signi cance, such as meeting the in situ production of biosurfactant in anoxic environments and the foamless fermentation of biosurfactants [8]. Aerobic production of rhamnolipids fails to meet the in situ applications in the anoxic environments, such as deep soil, oil reservoirs, sediments [8][9][10]. The foam problem in biosurfactant fermentation has been perplexing the production of biosurfactants [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mainly rhamnolipids producers, Pseudomonas aeruginosa, are facultative bacteria [8,13,14], only few studies have reported the anaerobic biosynthesis of rhamnolipids by rare P. aeruginosa strains [9,10,15,16]. P. aeruginosa can grow and metabolize at both aerobic and anaerobic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation